Bioactivity and antibacterial activity of strontium and silver ion releasing titanium. Issue 2 (6th August 2020) - Masamoto, Kazutaka; Fujibayashi, Shunsuke; Yamaguchi, Seiji; Otsuki, Bungo; Okuzu, Yaichiro; Kawata, Tomotoshi; Goto, Koji; Shimizu, Takayoshi; Shimizu, Yu; Kawai, Toshiyuki; Hayashi, Makoto; Morizane, Kazuaki; et al.
Abstract: To overcome problems associated with loosening of orthopedic implants and surgical site infections, we developed a novel, titanium (Ti)‐based material that releases both strontium and silver ions (CaSrAg–Ti) based on alkali‐and‐heat treatment. The results of commercially pure Ti (cp–Ti), Ti that releases Sr ions only (CaSr–Ti), and the novel CaSrAg–Ti material were compared. Mechanical tests were performed to evaluate the in vivo bonding properties of CaSrAg–Ti and the bone‐implant contact (BIC) ratio in histological specimens was determined at 4 and 8 weeks after implantation in a rat femur. Also, the in vitro antibacterial activities of this material against methicillin‐susceptible Staphylococcus aureus (MSSA) were evaluated after a 24 h incubation period by assaying colony‐forming units. In addition, antibacterial activities were evaluated in vivo at 7 days after implantation in a rat subcutaneous pocket model. There was direct contact between the bone and CaSrAg–Ti in histological specimens and no apparent signs of argyrosis in any rat. The bone‐bonding strength and the BIC ratio were increased by 2.7‐ and 2.3‐fold for CaSrAg–Ti vs. cp‐Ti at 4 weeks and 2.2‐ and 2.0‐fold at 8 weeks, respectively. As compared with cp‐Ti, the number of viable MSSA remaining on CaSrAg–Ti was reduced by 100 ± 0% in vitro and 94.2 ± 6.9% in vivo. Ti that releases Sr and Ag ions is a promising material that exhibits both bone‐bonding properties and anti‐MSSA activities.